RANCANG BANGUN WEB REPLIKA PADA WEBSITE E-COMMERCE - Baiq Dinasti Gita Purnama Putri; Anton Setiawan Honggowibowo; Anggraini Kusumaningrum (Compiler, 2016)
E-commerce or electronic commerce is an activity related to the purchase, sale, marketing of goods or services by using electronic systems such as the Internet or a computer network as a medium. In its development, e-commerce website has a lot of models and concepts, one of which is a replica website. Replica website is a reflection of the website host website itself. Website replica would be obtained if it had been making purchases on the website o f the parent (stta.name:8000) or web replica owned by a member (stta.name:8000/  sponsor=namaanggota). If you already have a replica website then the owner can sell online using the web replica, and can change the prices ofgoods as well as web background replicas. Besides being able to change the price and the background, a replica web owners are also entitled to a bonus from the purchase o f its products downline level 1. For the award is the excess of the price that has been modified with an initial price of a web master or web links above. From the calculation o f the questionnaire that was distributed to 30 respondents, the result of testing knowledge of web replica of 42.7% based on the assessment interval is Enough and application usage by 78.5%, which means Good.